1996
DOI: 10.1111/j.1440-1843.1996.tb00013.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of doxycycline as a pleural sclerosing agent in malignant pleural effusion: A prospective study

Abstract: To determine the efficacy of doxycycline in producing pleuroedesis in patients with malignant pleural effusion (MPE), 31 documented cases of MPE, aged 19-82 years were prospectively studied. Pleural sclerosis was done with 500 mg of doxycycline. Response regarding respiratory symptoms and pleural fluid accumulation were evaluated monthly. At one month, 27 patients were evaluable (4 dropped out). All responded and required no therapeutic thoracentesis. At 3 months, 13 patients dropped out, only 14 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 20 publications
0
15
1
2
Order By: Relevance
“…Doxycycline is used for treating a variety of infectious diseases in cancer patients (29,33,44). It has also been used previously for chemical pleurodesis in patients with malignant pleural effusions (15,39) and is currently being investigated as an antiangiogenic agent for the treatment of cancer (19,23). Administration of doxycycline to cancer patients could result in clinical chemotherapeutic failure as a consequence of generating P-gp-expressing, MDR tumor cell clones.…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline is used for treating a variety of infectious diseases in cancer patients (29,33,44). It has also been used previously for chemical pleurodesis in patients with malignant pleural effusions (15,39) and is currently being investigated as an antiangiogenic agent for the treatment of cancer (19,23). Administration of doxycycline to cancer patients could result in clinical chemotherapeutic failure as a consequence of generating P-gp-expressing, MDR tumor cell clones.…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline, a tetracycline analogue, has been recommended as a replacement for tetracycline. Although there are no direct studies comparing doxycycline with tetracycline, pleurodesis studies have demonstrated clinical success rates with doxycycline that are similar to those with tetracycline (historical data), with a success rate of up to 80-85% in carefully selected patients [120,126,127]. Most studies have recommended the utilization of 500 mg of doxycycline mixed with 50-100 cm 3 of sterile saline [120,127].…”
Section: Chemical Pleurodesismentioning
confidence: 99%
“…Although there are no direct studies comparing doxycycline with tetracycline, pleurodesis studies have demonstrated clinical success rates with doxycycline that are similar to those with tetracycline (historical data), with a success rate of up to 80-85% in carefully selected patients [120,126,127]. Most studies have recommended the utilization of 500 mg of doxycycline mixed with 50-100 cm 3 of sterile saline [120,127]. As pain is the most common complication associated with doxycycline pleurodesis, narcotic analgesic and/or conscious sedation is often recommended [126].…”
Section: Chemical Pleurodesismentioning
confidence: 99%
“…Doxycycline, a tetracycline analog, demonstrated clinical success rates that are similar to those of tetracycline, up to 85% in carefully selected patients [61,88]. Most studies have recommended the utilization of 500 mg of doxycycline mixed with 50-100 ml sterile saline [61,89].…”
Section: Tetracycline and Doxycyclinementioning
confidence: 99%